2007
DOI: 10.1007/s11218-007-9017-z
|View full text |Cite
|
Sign up to set email alerts
|

Cultural models of education in American Indian, Asian American and European American contexts

Abstract: Three studies examined models of education among American Indian (AI), Asian American (AA), and European American (EA) students. Cultural models of education are patterns of ideas and practices relevant to schools, teachers, and self that mediate and regulate behavior in the academic domain. In study 1, mainstream university students (N = 148) and AI University students (N = 187) viewed education as a tool for success. AI, however, generated more mentions of education as a tool for community success and more n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 55 publications
4
116
0
2
Order By: Relevance
“…Reprenant l'idée que l'école véhicule certaines valeurs et normes culturelles, les tenants de l'approche socioculturelle ont cherché à objectiver la non neutralité des institutions. Les travaux montrent que les universités, notamment aux Etats-Unis, promeuvent des normes d'indépendance (Fryberg & Markus, 2007). Il est attendu des étudiants qu'ils développent et expriment leurs propres opinions, qu'ils travaillent en autonomie et apprennent à remettre en cause les normes plutôt qu'écouter l'avis d'autrui ou respecter les règles (Stephens, Fryberg, Markus, Johnson, & Covarrubias, 2012).…”
Section: Approche Socioculturelle De La Classe Socialeunclassified
“…Reprenant l'idée que l'école véhicule certaines valeurs et normes culturelles, les tenants de l'approche socioculturelle ont cherché à objectiver la non neutralité des institutions. Les travaux montrent que les universités, notamment aux Etats-Unis, promeuvent des normes d'indépendance (Fryberg & Markus, 2007). Il est attendu des étudiants qu'ils développent et expriment leurs propres opinions, qu'ils travaillent en autonomie et apprennent à remettre en cause les normes plutôt qu'écouter l'avis d'autrui ou respecter les règles (Stephens, Fryberg, Markus, Johnson, & Covarrubias, 2012).…”
Section: Approche Socioculturelle De La Classe Socialeunclassified
“…Research framed by cultural psychology found, consistently, that causal attribution beliefs are culturally embodied (Fryberg and Markus, 2007;Heine, Lehman, Markus, and Kitayama, 1999;Holloway, 1988;Li, 2003;Markus and Kitayama, 1991;Okagaki, 2001). This literature reports that Americans attribute success and failure to ability.…”
Section: Findings Consequences Of Literacymentioning
confidence: 97%
“…Research framed by cultural psychology found, consistently, that causal attribution beliefs are culturally embodied (Fryberg and Markus, 2007;Heine, Lehman, Markus, and Kitayama, 1999;Holloway, 1988;Li, 2003;Markus and Kitayama, 1991;Okagaki, 2001). Comparing attribution theories in American and Asian cultures, this literature reports that whereas Asians attribute success and failure to effort, Americans attribute them to ability.…”
Section: Adults' Perceptions Of the Good And Poor Readersmentioning
confidence: 99%